Improved diabetes medication convenience and satisfaction in persons with type 2 diabetes after switching to insulin glargine 300 U/mL: results of the observational OPTIN-D study. Issue 1 (1st October 2018) - Wieringa, Thomas H; de Wit, Maartje; Twisk, Jos WR; Snoek, Frank J
Abstract : Objective: Insulin glargine 300 (Gla-300) provides less hypoglycemia risk and more flexibility in injection time. The extent to which these effects translate into improved patient-reported outcomes (PROs) is unknown, and is the subject of this observational study. Research design and methods: Adults with type 2 diabetes treated with basal insulin for at least 6 months initiating Gla-300 were included. Data were collected at baseline (start Gla-300) and at 3-month and 6-month follow-up. Patients and physicians gave reasons for switching to Gla-300 at baseline and the extent to which Gla-300 fulfilled their expectations at 6 months. Mixed model analyses examined PRO changes over time, with emotional well-being (WHO-5 Well-Being Index) as the primary outcome. The secondary outcomes were hypoglycemia incidence, hemoglobin A1c (HbA1c), hypoglycemia worries (worry subscale of the Hypoglycemia Fear Survey), diabetes distress (short form of the Dutch version of the Problem Areas In Diabetes Scale), diabetes medication convenience (Diabetes Medication System Rating Questionnaire (DMSRQ)), sleep quality and duration (Pittsburgh Sleep Quality Index), and adherence (Summary of Diabetes Self-Care Activities). Results: 162 patients participated: 53.70% were men, the mean age was 65.54 years (9.05), baseline mean HbA1c was 7.87% (1.15) (62.48 mmol/mol (12.61)), and mean diabetes duration was 15.14 years (6.65). Mean WHO-5 Well-Being Index scores improved non-significantly from 61.94 (19.52) at baseline (T0) to 63.83 (19.67) at 6 months (T2). Mean DMSRQ scores improved significantly from 32.96 (9.02) (T0) to 36.70 (8.85) (T2) (p<0.001). Dose (less volume) was a switching reason in 69.60% of patients and 63% of physicians, and flexibility in 33.30% and 24.70%, respectively. Gla-300 fulfilled the expectations or even better than expected in 92.30% of patients and 88.90% of physicians. Conclusion: In a relatively well-controlled sample of adults with type 2 diabetes, switching to Gla-300 improves diabetes medication convenience.